Emerging contractual and legal risks from the application of building information modelling. Issue 10 (26th June 2019) - Almarri, Khalid; Aljarman, Moshabab; Boussabaine, Halim
Abstract : Purpose: There has been a mounting interest in building information modelling (BIM) in the construction industry sector worldwide due to its perceived benefits. However, reliance on information technology is associated with risks. The purpose of this paper is to offer a better understanding of the emerging contractual and legal risks, which might influence the successful adoption of BIM, in order to facilitate the successful implementation of BIM in the construction industry. Design/methodology/approach: The risks used in the study were documented from the literature, and primary data were collected by a questionnaire survey. The analysis of the results was driven by univariate and inferential statistics (Analysis of Variance) to identify the emerging contractual and legal risks. Findings: The findings showed that there were little significant differences in the mean rating of the occurrence of contractual and legal risks between the respondents. The study confirmed that emerging risks are likely to be related to BIM documentations, intellectual rights and liability, missing data and misplaced assumptions among project stakeholders. The results showed that BIM success depends on close collaboration, at the outset of the project, with the client, designers, contractors and consultants. Practical implications: The findings suggest that contract documents and contract agreements may need to be created in accordance with the identified risks, so that the questions of contractual and legal responsibilities are appropriately defined and allocated among the participants. Originality/value: Important legal and contractual risks have been identified in the application of BIM. It renders a new understanding of the risks that might influence the successful adoption of BIM.